2005
DOI: 10.1073/pnas.0408624102
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the ergothioneine transporter

Abstract: Variants of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
482
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 479 publications
(514 citation statements)
references
References 27 publications
15
482
2
Order By: Relevance
“…When mouse OCTN1 or OCTN2 was heterologously transfected in HEK293 cells, only OCTN1, but not OCTN2 efficiently transports ergothioneine as a substrate (Figure 2A), as previously reported for human and rat OCTN1 (3,19). The uptake of [ 3 H]ergothioneine by mouse OCTN1 was saturable with Km and Vmax values of 4.68 µM and 532 pmol/min/mg protein, respectively ( Figure 2B) and reduced by the replacement of Na + in the medium ( Figure 2C).…”
Section: Ergothioneine Is a Substrate Of Mouse Octn1mentioning
confidence: 54%
See 1 more Smart Citation
“…When mouse OCTN1 or OCTN2 was heterologously transfected in HEK293 cells, only OCTN1, but not OCTN2 efficiently transports ergothioneine as a substrate (Figure 2A), as previously reported for human and rat OCTN1 (3,19). The uptake of [ 3 H]ergothioneine by mouse OCTN1 was saturable with Km and Vmax values of 4.68 µM and 532 pmol/min/mg protein, respectively ( Figure 2B) and reduced by the replacement of Na + in the medium ( Figure 2C).…”
Section: Ergothioneine Is a Substrate Of Mouse Octn1mentioning
confidence: 54%
“…In addition, Gründemann et al have previously reported that ergothioneine is also the good substrate for OCTN1 in vitro, by utilizing cell biological and metabolomics approaches (3). Despite the previous identification of various substrates for OCTN1 in in vitro experimental systems, biologically important substrates for OCTN1 in vivo have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, EGT is concentrated in erythrocyte progenitor cells, monocytes, the intestine and kidneys. EGT is cell membrane impermeable and recent human studies have identified a specific plasma membrane bound organic cation transporter known as OCTN1, which is encoded by the gene SLC22A4 (Grundemann et al, 2005). Polymorphisms in SLC22A4 have been associated with diabetes (Santiago et al, 2006) and susceptibility to chronic inflammatory diseases such as Crohn's disease (Fisher et al, 2006;Leung et al, 2006;Peltekova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…OCTN1/SLC22A4 is multispecific transporter which accepts various types of therapeutic agents as substrates [5,6]. Metabolome analysis using cell lines transfected with SLC22A4 gene in vitro and octn1/slc22a4 gene knockout (octn1 -/-) mice in vivo have demonstrated that OCTN1 most efficiently transports a naturally occurring 5 food-derived antioxidant, ergothioneine (ERGO) [7,8]. ERGO is highly hydrophilic, and its uptake through plasma membranes is primarily mediated by OCTN1, as evidenced by the fact that food-derived ERGO is detected at µM to sub-mM level in almost all organs in wild-type mice, but minimally detected in octn1 -/-mice [8].…”
Section: Introductionmentioning
confidence: 99%